Needs Analysis of Physics Learning Media Integrated Local Wisdom - Eliezanatalie, Syahda; Deta, Utama Alan (International Journal of Research and Community Empowerment, 2023)
Indonesia is a country that is rich in cultural diversity, but it is starting to fade along with technological developments. Preservation of local wisdom is needed, one of which is by integrating it into physics learning. This study aims to analyze the needs of physics learning media integrated with local wisdom in schools. The research method used is a qualitative descriptive research method, namely by conducting a needs analysis. The research was conducted in September 2022 - October 2022 at SMA Labschool Unesa 1 Surabaya. The research results show that the learning media used are not varied. Teachers have not played a big role in developing learning media, especially related to local wisdom or culture around them. This research is expected to explain the concept of physics that can connect modern science with ethnoscience in traditional games and can be used as physics learning materials.